“Caracterización de los suelos de las provincias de San Martín y Picota con finas de determinar su capacidad de uso mayor” - López Fulca, Roaldo (2002)
The present study was carried out in the counties of San Martín and Picota in the San Martín Región. The study was of the best soil samples found in these counties, for which field proyects had to be carried out that consisted of the excavation of 63 trial pint. The whole study area consisted of 79 040 hectacres. Having the tria! pint allowed you to proceed whith the profile study soil samples are removed and sent to the laboratories of the Agrarian National University in La Molina, for the respective results of their physical and chemical analysis. The obtaines results allows you to interpret the chemical and physical characteristics of the soils in the present work. From the results, we learn that the best asils, in the areas of textura and structure are found in Juan Guerra, Chazuta, Utcurarca, Buenos Aires, Paujilzapa, Pucacaca, Sauce, Santo Tomas and Mariscal Castilla. The subsector of San Antonio of Cumbaza, Banda de Shilcayo, Morales, Chazuta and Sauce present a reaction moderately acid to neutral and with a wealth as for as available phosphorus. While the soils of Cacatachi, Juan Guerra, Yacucatina, Utcurarca, Buenos Aires, Paujilzapa, Pucacaca and Leoncio Prado show a reaction moderately alkaline to neutral whith a high conterit of available potassium, interchangeable cationes and carbonates. By means of the use of the classification of Lands (D.S. 00€?8-75-AG) and based on the obtained characteristics, the following groups of greatest -capacity have been determined. Maximun Capacity Useage A 56 872 hectacres. Maxirnun Capacity Useage C Maxirnun Capacity Useage P Maxirnun Capacity Useage 3 094 hectacres 17 650 hectacres 1 424 hectacres. These characteristics lead us to cultivation zones in the following way. Ali the selsin class A present excellent conditions for the cultivation of rice and other cultivation. The lirniting factor in rnany being water and in thers being the topography. Few areas present lirnitations in deph. There are sorne areas of P and F that can be dedicated rnainly to perrnanent cultivations, but white applying sorne rneasures of control and handling of soils of the cultivations, in view that those areas are topographically different to others.